(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Therapeutic Plasma Exchange (TPE) is an effective therapeutic procedure for treating Myasthenia Gravis (MG). Objectives: The aim of study was to evaluate demographics, indications, adverse reactions and outcome of therapeutic plasma exchange in myasthenia gravis patients. Methodology: This prospective observational study was conducted in the Department of Transfusion Medicine at National Institute of Neurosciences and Hospital (NINS&H), Dhaka, Bangladesh from August 2014 to June 2022. All patients with Myasthenia Gravis who received therapeutic plasma exchange as a treatment during hospitalization were included in this study. Data were systematically recorded and these were variables of demographics, clinical indications, numbers of sessions, volume of exchanged plasma, clinical responses and complications during or after the procedure. Results: A total number of 72 patients had undergone 275 sessions of therapeutic plasma exchange among which 52(72.2%) cases were male and the mean age was 39.5±13.11 years. For each patient the number of therapeutic plasma exchange session and volume of plasma exchange were 3.69±1.016 (Range 2 to 7) and 2266.7±361.53 ml (Range 1400 to 3100) respectively. Anti-acetylcholine receptor antibody (Anti-ACR Ab) was positive in 44(61.1%) cases. Myasthenic crisis (n=45, 62.5%) was the most common indication of therapeutic plasma exchange followed by preoperative preparation for thymectomy (n=16, 22.2%) and worsening of myasthenic weakness (n=11, 15.3%). In 275 sessions of therapeutic plasma exchange, overall incidence of adverse reaction was in 26(9.45%) cases. Mild allergy (n=9, 3.27%) and pyrexia (n=5, 1.82%) were most commonly reported. Hypotension was reported in 4(1.46%) cases. Reactions were mild and were reversed by bed side managements. Response to treatment was observed in 80.5% (n=58) patients. 2(2.8%) patients of Myasthenia Gravis died; but death was unrelated to therapeutic plasma exchange. Conclusion: Therapeutic plasma exchange is rapidly effective therapy for myasthenic crisis, progressive myasthenia gravis and prior to thymectomy operation and it has adequate safety profile. Journal of National Institute of Neurosciences Bangladesh, January 2023;9(1):16-23